Methodology for Collaborative Management of Makarenko and Adizes - Ilaltdinova, Elena Yu.; Lebedeva, Irina V.; Frolova, Svetlana V.; Arifulina, Ramila U.; Aksenov, Sergey I. (International Review of Management and Marketing, 2016)
The research is based on the comparative content analysis of the recent works on management by I. Adizes and works by A. Makarenko published in modern Russian edition (2008-2015) in 8 volumes which has overcome shortcomings of soviet time editions having some ideologically bound assumptions. The analysis of key terminology and basic notions of company management methodology of I. Adizes and educational institution (commune) management methodology of A. Makarenko allowed to single out the common specific features of Methodology for Collaborative Management in modern American and earlier Russian-Ukrainian versions. The main common concept is that of the development as a form of life or existence of the company. There are some similarities and differences in interpretation of the development or change. The common key concepts of Methodology for Collaborative Management adjusted for languages differences are mutual trust, respect, complementary team, stages of corporate life-cycle, change management, mission. The difference is shown in the understanding of the stages of corporate life-cycle: in Makarenko’s interpretation in it is more detailed at the beginning stages and more optimistic concerning its inevitable death as Adizes describes it. Keywords: management, collaborative management, Adizes, Makarenko JEL Classifications: B21, D21, M21